Treatments for Persistent Genital Arousal Disorder in Women: A Scoping Review - Martín-Vivar, María; Villena, Alejandro; Mestre-Bach, Gemma; Hurtado-Murillo, Felipe; Chiclana Actis, Carlos (Journal of Sexual Medicine, 2023)
Background: Persistent genital arousal disorder (PGAD) is characterized by elevated discomfort associated with persistent genital arousal in the absence of sexual desire. Aim: To perform a scoping review of the proposed treatments for PGAD and their efficacy. Methods: A scoping review was carried out (PRISMA-Scr) that included articles on PGAD as the main disorder, only in women, which explained, in detail, the treatment and its efficacy, was empirical, was written in English and Spanish. No prior filtering by years was performed. Outcomes: Three different effective treatments were found (Physical therapies, pharmacological therapies, and psychotherapeutics in combination with other therapies). Results: Thirty-eight articles were selected. From physical therapies, treatments using neuromodulation, transcutaneous electrical stimulation, Botox, surgery, electroconvulsive therapy, manual therapy, pelvic floor therapy, dietary changes, and transcranial magnetic stimulation showed effectiveness. Using the pharmacological approach, paroxetine, duloxetine, pramipexole, ropinirole, and clonazepam treatments were effective. Psychotherapy treatments showed effectiveness only in combination with other types of treatments, specifically a combination of cognitive–behavioral strategies with pharmacological treatment. Clinical implications: Pharmacological treatment, specifically SSRIs, have proven to be the therapy of choice for different subtypes of patients. Strengths and limitations: This study analyzed treatment effectiveness with different approaches and took into consideration those articles where psychotherapy was used as a combination treatment with pharmacological and physical therapy. The main limitation is that it was focused exclusively on women, and the results cannot be generalized to include men. Conclusions: To date, a combination of pharmacological interventions with physical therapy and, in some occasions, with psychological therapy is main strategy followed to accomplish effective treatment of PGAD. Martín-Vivar M, Villena-Moya A, Mestre-Bach G, et al. Treatments for Persistent Genital Arousal Disorder in Women: A Scoping Review. J Sex Med 2022;19:961–974.
Keywords: female sexual dysfunction; persistent genital arousal disorder; persistent sexual arousal syndrome; sexual arousal disorders; Scopus